Feasibility of coal bottom ash as fine aggregate in strain-hardening cementitious composites: A study on strength, durability, and sustainability - Abdulkadir I.; Ean L.W.; Wong L.S.; Murali G.; Mohammed B.S.; Amin N.A.M.B.M.; Jaafar R.A.H.B.R. (Elsevier Ltd, 2025)
The search for cost-effective and sustainable materials for strain-hardening cementitious composites (SHCC) has led researchers to explore alternatives to silica sand, a critical yet costly and environmentally unfavorable material. Although river sand seems like a cheaper and viable alternative, its extraction is linked to severe environmental degradation. This study aims to investigate the potential of coal bottom ash (CBA) as a replacement for silica sand in SHCC, targeting to meet the minimum requirements for structural applications. The novelty of this research lies in its comprehensive exploration of CBA as a partial to full replacement for silica sand (at 0 %, 25 %, 50 %, 75 %, and 100 %), extending beyond the replacement limit investigated in previous studies on SHCC, and provides an extensive evaluation of the composite's fresh, mechanical, durability, and microstructural properties. Additionally, it includes a thorough assessment of the leaching potential, CO? emissions, energy consumption, and cost implications of the CBA-SHCC, which have not been fully explored in earlier CBA-SHCC research. The findings indicate that the reduction in mechanical strength was minimal (0.5 %-10 %) across all CBA replacement levels. Notably, all mixes demonstrated typical strain-hardening behavior, sustaining higher flexural loads beyond the first crack, with increased deflection capacity observed at higher CBA contents, peaking at 50 % replacement. Durability metrics, including water absorption and HCl acid attack resistance, exhibited a downward trend with higher CBA content but remained within acceptable limits up to 75 % replacement. Toxicity characteristic leaching procedure results confirmed the non-leachability of toxic elements in both the CBA and CBA-SHCC mixes. Economically and environmentally, CBA proved advantageous, resulting in 1.5?5 % lower CO2 emissions, 0.4?1.5 % lower energy consumption, and 18?84 % cost savings at 25?100 % CBA replacement. Additionally, a multicriteria analysis using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) was employed, which identified 25 % as the optimal CBA content that balances fresh properties, mechanical strength, durability, environmental sustainability, and cost efficiency. The study is significant because it demonstrated that CBA can be used as a sustainable and cost-effective alternative to silica sand in SHCC, with lower environmental impact while maintaining structural integrity. ? 2024 Elsevier Ltd